Changing Assessment of the Educational Institution Manager’s Competencies in Lithuania - Liukinevičienė, Laima; Antanavičienė, Lina (Socialiniai tyrimai, 2018)
Education is one of the key areas in the development of a democratic state. Educational institutions and organizations are keen on innovations, therefore, certain public administration initiatives are often primarily and successfully implemented here. This also applies to the assessment of managers’ competencies and the development of leadership competencies as well. In recent decades, Lithuanian scientists have been intensively analyzing the experience gained in other countries while evaluating competencies of the heads of educational institutions and actively participating in the development of competence assessment tools. At present, the state of Lithuania has reached the stage where the assessment systems have already been tested and improved several times. Currently, applying the analytical content analysis of theoretical sources and other resources alongside, the aim is to summarize the developmental process of the manager’s competence assessment in Lithuania in 1998–2018, and highlight the key factors that have influenced the changing evaluation criteria.Having acknowledged the research-based truths (the manager’s competence assessment is necessary for the long-term effectiveness of the institutional activities; direct link between the results of an institution and the competencies of its leader is obvious; the content of the competency-packet necessary in order to control the continuous management is inclined to change; the LR evaluation system currently applied to the executivemanagers needs improvement; the LR system for improving managerial competencies of educational institution leaders is still being created, etc.), the necessity of regular periodical competence assessment and the need to constantly review the evaluation criteria and the models, seeking to improve them, are perceived.According to M. Fullan (1991), the most significant factor influencing the change in educational reforms is political, as educational reforms require a lot of resources. The analysis of the competence assessment of educational institution managers performed in the Republic of Lithuania confirms this statement. The need for high-level managerial competency-packet is highlighted in the following documents: programs of the main political parties seeking power over 20 years; Government programs of the Republic of Lithuania; educational strategies developed as part of the educational management structure; programs initiated, etc. The influence of EU education policy is obvious. The EU institutions provide general guidance to Member States, however, the initial training of educational institution managers and the improvement of their qualifications, the competence requirements and the recruitment procedures for the leaders/heads of educational institutions as well as their further career options are treated as an individual country’s project.Having in mind the practical division of the implementation of Lithuanian educational reform into separate stages that is taken for granted in the Lithuanian educational management, we are constantly monitoring the continuous improvement of the management assessment process:1990–1997. Reorganization of the Education System; requirements for the qualifications of the educational institution managers were regulated by the Law on Education of the Republic of Lithuania (1991).1998–2002. The period was marked by the introduction of managerial attestation based on the three categories of a manager’s competence associated with the degree of change in the supervised institution. In accordance with the procedure approved by the Order of the Minister of Education and Science of the Republic of Lithuania “Qualification Requirements for Heads of State and Municipal Educational Institutions, their Appointment and Dismissal” (1998) that contains the main general and special requirements for applicants. The document of 1999 was supplemented with detailed descriptions of advantages and areas of the professional competency-packet of a manager and the updated managerial competence.2003–2012. The competencies of the head of an educational institution were described and the competence assessment started to be applied to recruitment according to the description of competencies. The requirements were presented in the “List of Qualification Requirements for Heads of Schools of all Types (except higher education institutions)” (2005). Essential and obligatory managerial competencies were described in the “Competence Profile of the School Head” (2007). The document “Description of Managerial Qualification Requirements for State and Municipal Educational Institutions (except higher education institutions)” (2011) identified the leadership competence areas and the general competence areas and the managerial assessment (self-evaluation of one’s performance and skills when working with people). General competencies make the assessment of school managers closer to the civil servants’ assessment.The current period (2013–2022). Competence requirements for the general education school heads are as follows: Master’s degree; 5 Competence Levels of management in the educational institution; mastered level B1 of one of the EU working languages; requirement for an impeccable reputation, etc. The system of competence assessment has been implemented since 2011, and it has constantly been improved until this day, 2018. In 2011, the centralized model was implemented (evaluation performed by the National School Assessment Agency). In 2015–2017, the 2-stage assessment model was introduced according to which the institution authorized by the Ministry started evaluating most of the general competencies, and the organizer of the competition rated most of the competence assessment in the management areas. In 2018, a different level was set for each compulsory competence. At present, the variety of evaluation methods and forms is increasing, requirements for the assessors are getting higher, and social partners are participating as the assessment commission members.Performed developmental analysis shows the growing requirements for the institutional management and leadership and the ability to work with local authorities as well as local and foreign partners. Improvement of the managerial assessment in the Lithuanian Republic is carried out in a consistent manner, and it is linked to the assessment of civil servants’ competencies. These processes match up with the political decisions of the state. Influence of the researchers working in the field of public administration and leadership is evident in the formation of the managerial assessment system as well as in the creation of a system for the managers’ development.
Keywords: assessment system; assessment of managerial competencies; head of educational institution